2016
DOI: 10.1097/brs.0000000000001226
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-221 Regulates Hypertrophy of Ligamentum Flavum in Lumbar Spinal Stenosis by Targeting TIMP-2

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…The number of comprehensive 'omics' studies to elucidate the molecular pathology of LF degenerative hypertrophy in LSS patients has been increasing 7,14,15) . In these cases, LF samples from LDH patients, for which the age group is often younger than that of patients with LSS, were used as controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of comprehensive 'omics' studies to elucidate the molecular pathology of LF degenerative hypertrophy in LSS patients has been increasing 7,14,15) . In these cases, LF samples from LDH patients, for which the age group is often younger than that of patients with LSS, were used as controls.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al compared LSS and LDH samples and showed that the level of miR-155 in the LF was associated with LF thickness (r=0.958, p<0.01), and the mRNA and protein expression levels of type I and III collagen were increased 20) . Xu et al employed a microarray technique to samples from patients with LSS and LDH, miR-221, whose expression level was increased in the LF from patients with LSS, regulates LF hypertrophy by suppressing TIMP2, which inhibits the degradation of type I and III collagen, and consequently increases the amount of these collagens 7) . In this study, neither these miRNAs were extracted as those significantly related to LF hypertrophy; however, miR-29c and miR-223, which were identified as age-related miRNAs in this study, were also listed as differentially expressed miRNAs by Xu et al 7) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that the initial stage of hypertrophic LF is associated with different cytokines, including TGF-β and VEGF secreted by degenerated and herniated intervertebral disks and facet arthrosis [11]. With the progression of intervertebral space instability and chronic inflammation, a high degree of macrophage infiltration was identified as a major cellular source of various molecules [12], including matrix metalloproteases (MMPs) [13, 14], tissue inhibitors of matrix metalloproteases (TIMPs) [15, 16] during LF hypertrophy. The LF ECM can become disorganized and show decreased levels and degeneration of elastic fibers and increased levels of collagen fibers [17].…”
Section: Discussionmentioning
confidence: 99%